Social ulighed i sundhed i et udsat boligområde: En undersøgelse af sammenhængen mellem selvvurderet helbred, etnicitet og social position - Kronborg Bak, Carsten; Tanggaard Andersen, Pernille (Nordisk Tidsskrift for Helseforskning, 2014)
The purpose of this study was to investigate the association between self-rated health, ethnicity and social position in a deprived neighbourhood in Denmark where many residents have a non-western background. In the article we investigate associations between self-rated health as dependent variable and ethnicity and social position (defined by an “index for resources of living conditions”) as independent variables. The study is based on survey data collected in a geographically bounded and socially deprived neighbourhood. The analyses were conducted by logistic regression models.The results shows a strong connection between the residents “social position” and their self-rated health. In this investigation we were not able to identify any connection between ethnicity and self-rated health which indicates that ethnicity does not constitute an explanation per se for differences in self-rated health.